2021
DOI: 10.1002/jbm.b.34842
|View full text |Cite
|
Sign up to set email alerts
|

Biological compatibility, thermal and in vitro simulated degradation for poly(p‐dioxanone)/poly(lactide‐co‐glycolide)/poly(ethylene succinate‐co‐glycolide)

Abstract: Bio‐absorbable polymers are widely desired to be applied and used as biomaterials for surgery hemostatic and medical tissue engineering devices. Ring‐opening copolymerization reaction was applied to synthesize poly(ethylene succinate‐co‐glycolide) (PES‐b‐PGA). Stannous octoate was used as a catalyst whereas poly(ethylene succinate) was used as a macro‐initiator to react with glycolide. PES‐b‐PGA was then used as a compatibilizer to prepare the blend biomaterial of PPDO/PLGA/PES‐b‐PGA by melt blending poly(p‐di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The recent use of polymeric biomaterials in transplantation studies, such as PLGA, PCL, and PEG, showed good biocompatibility, including cellular response, cell adhesion, and hemocompatibility [95,96]. Biocompatibility may be further enhanced by modification or addition of other polymeric materials [97][98][99][100]. For those nanoparticles, the ISO standard 1099-22 test that is dedicated to assessing the impact of shape, size, surface charge and function, dispersion state, matrix composition, attached protein formation on cell viability, and endocytosis process have been described [101,102].…”
Section: Biocompatibility and Safetymentioning
confidence: 99%
“…The recent use of polymeric biomaterials in transplantation studies, such as PLGA, PCL, and PEG, showed good biocompatibility, including cellular response, cell adhesion, and hemocompatibility [95,96]. Biocompatibility may be further enhanced by modification or addition of other polymeric materials [97][98][99][100]. For those nanoparticles, the ISO standard 1099-22 test that is dedicated to assessing the impact of shape, size, surface charge and function, dispersion state, matrix composition, attached protein formation on cell viability, and endocytosis process have been described [101,102].…”
Section: Biocompatibility and Safetymentioning
confidence: 99%